La libertad moral - Nogales Naharro, Mª De Los Ángeles (Anuario de Derechos Humanos. Nueva Época, 2010)
Considering Ethics as the science which studies the morality of human acts, in our essay we are going to analyze freedom as a constituent element of them. The possibility for the man to orientate his operations from the faculties from which they spring towards a good or bad purpose, reveals human freedom, this is, the fact that he is not determined by his own nature towards a unique direction. It is our purpose to show in this essay that it is possible for the man to posses himself in the way of the rational self-domination of his will power, and that self-conquest, on which moral freedom lies, leads to a progress in his self-knowledge, a necessary requirement for social progress.
Keywords: Freedom; Ethics; Human act; Perfection; Progress; Moral freedom